Application of Capillary Electrophoresis with Laser-Induced Fluorescence to Immunoassays and Enzyme Assays - Binh Thanh Nguyen; Kang, Min-Jung (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Capillary electrophoresis using laser-induced fluorescence detection (CE-LIF) is one of the most sensitive separation tools among electrical separation methods. The use of CE-LIF in immunoassays and enzyme assays has gained a reputation in recent years for its high detection sensitivity, short analysis time, and accurate quantification. Immunoassays are bioassay platforms that rely on binding reactions between an antigen (analyte) and a specific antibody. Enzyme assays measure enzymatic activity through quantitative analysis of substrates and products by the reaction of enzymes in purified enzyme or cell systems. These two category analyses play an important role in the context of biopharmaceutical analysis, clinical therapy, drug discovery, and diagnosis analysis. This review discusses the expanding portfolio of immune and enzyme assays using CE-LIF and focuses on the advantages and disadvantages of these methods over the ten years of existing technology since 2008.